ANALISIS FUNDAMENTAL DAN RESIKO SISTEMATIK TERHADAP HARGA SAHAM PERBANKAN YANG TERDAFTAR PADA INDEKS LQ 45 - Amanda WBBA; Wahyu Ario Pratomo (Ekonomi dan Keuangan, 2013)
This research aimed to determine the effect of fundamental’s aspect and systematic risk to the stock price of bank on the list of LQ 45. Fundamental analysis is a picture of the bank company’s performance based on fundamental aspects. Systematic risk (BETA) is a risk that affects the market price of the existing shares on the stock exchange. Fundamental analysis is the form of financial ratios and Beta are identified variables could affect the stock price. The variables used in this research are financial ratios, Return on Assets (ROA), Return on Equity (ROE), Debt to Equity Ratio (DER), Earning Per Share (EPS) Price Earning Ratio (PER), and Beta. Beta is a risk systematic sensitivity indicator of the stock market. This research used panel data which is a combination of the data time-series and cross-section with multiple linear regression models. The data was then estimated by Fixed Effect Model (FEM) and processed with the program Eviews 7. The results showed that the independent variables, Debt to Equity Ratio (DER), Earning Per Share (EPS), Price Earning Ratio (PER) and BETA significant affected on bank stock prices LQ 45 while the Return On Assets (ROA) and Return on Equity (ROE) not significant affected on bank stock prices LQ 45. The independent variables used in this research are affected the stock price of bank in LQ 45 as the dependent variable with R-square 0.988096 and probability 0.000000. Keywords:  Return On Assets (ROA), Return On Equity (ROE), Debt to Equity    Ratio (DER), Earning Per Share (EPS), Price Earning Ratio (PER), Systematic Risk (BETA)